2014
DOI: 10.7554/elife.03293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of motor neurons and a mechanosensitive sensory neuron in the defecation circuitry of Drosophila larvae

Abstract: Defecation allows the body to eliminate waste, an essential step in food processing for animal survival. In contrast to the extensive studies of feeding, its obligate counterpart, defecation, has received much less attention until recently. In this study, we report our characterizations of the defecation behavior of Drosophila larvae and its neural basis. Drosophila larvae display defecation cycles of stereotypic frequency, involving sequential contraction of hindgut and anal sphincter. The defecation behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…However, NOMPC channels and their homologs may serve multiple functions in different mechanosensors (Chadha et al, 2015; Effertz et al, 2011; Kang et al, 2010; Lehnert et al, 2013; Ramdya et al, 2015; Sidi et al, 2003; Yan et al, 2013; Zhang et al, 2013; Zhang et al, 2014), and their functions may be regulated differently in different cell types. It is conceivable that in different mechanosensors, NOMPC interacts with different sets of molecules that regulate channel opening in vivo , a possibility that warrants future investigation for better understanding of the mechanical gating machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NOMPC channels and their homologs may serve multiple functions in different mechanosensors (Chadha et al, 2015; Effertz et al, 2011; Kang et al, 2010; Lehnert et al, 2013; Ramdya et al, 2015; Sidi et al, 2003; Yan et al, 2013; Zhang et al, 2013; Zhang et al, 2014), and their functions may be regulated differently in different cell types. It is conceivable that in different mechanosensors, NOMPC interacts with different sets of molecules that regulate channel opening in vivo , a possibility that warrants future investigation for better understanding of the mechanical gating machinery.…”
Section: Discussionmentioning
confidence: 99%
“…NOMPC fulfills essentially all the criteria for a bona fide mechanotransduction channel and mediates touch sensation in Drosophila larvae (Arnadottir and Chalfie, 2010; Yan et al, 2013). NOMPC is also involved in hearing of Drosophila larvae and adults (Bechstedt and Howard, 2008; Effertz et al, 2011; Kamikouchi et al, 2009; Lehnert et al, 2013; Liang et al, 2011; Zhang et al, 2013), collective behavior of adult flies (Ramdya et al, 2015), proprioception at adult leg joints (Chadha et al, 2015), as well as tension sensing in the hindgut of larvae (Zhang et al, 2014). NOMPC forms functional mechanotransduction channels in heterologous expression systems (Gong et al, 2013; Yan et al, 2013), thus facilitating structure-function studies of its mechanosensitivity (Zanini and Göpfert, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Complex, muscle-driven physiological processes, such as peristaltic contractions to move the content of the gut or heartbeat, require IC systems to control them. For example, during defaecation behaviour in the fly, the hindgut and anal sphincter are driven by the sequential activation of motorneurons [54], representing an IC system. The motorneurons also receive sensory feedback from a mechanosensory neuron in the anus, adding an IO component to the circuit [54].…”
Section: Internal Coordination and Input-output Systems For The Neuramentioning
confidence: 99%
“…A fascinating study investigating the regulation of defecation behavior has suggested a link between enteric neurons and intestinal muscle (Zhang et al, 2014). The motor neurons innervating the hindgut and anal sphincter cooperate with the intestinal muscle to control defecation activity (Zhang et al, 2014). Although striking advances have been made in recent years, the exact regulatory network of links between enteric neurons and the intestine is only partly understood.…”
Section: Links Between Larval Organsmentioning
confidence: 99%